DOI: 10.22215/etd/2017-11965
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Flexibility in the Context of Stress and Depressive Disorders

Abstract: Disturbances of cognitive flexibility may contribute to difficulties in emotion regulation, which can lead to the emergence of depressive illness. However, there are limited data available as to how stressful experiences influence cognitive flexibility. The purpose of the present research was to examine the contribution of different stressor experiences, including selfreported early-life trauma, on cognitive flexibility, and how disturbances in this regard were related to heightened depressive symptoms and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 199 publications
(410 reference statements)
2
1
0
Order By: Relevance
“…This was somewhat surprising, given the abundance of past research indicating that diet may be predictive of cognition (e.g., Freeman, Haley-Zitlin, Rosenberger, & Granholm, 2014), coping (e.g., Kuczmarski et al, 2017), and depression (e.g., O'Neil et al, 2014). The present findings also revealed that both dimensions of cognitive flexibility (cognitive control and cognitive resources) were highly correlated, and that both dimensions were negatively associated with emotion-focused coping, typical and atypical depressive symptoms, and that only cognitive resources was positively correlated with problem-focused coping, which is in line with previous research (Gabrys, Anisman, & Matheson, 2018). In addition, persistent use of emotion-focused coping was related to both types of depression, and problem-focused coping was negatively related to typical depressive symptoms, which again corresponded with past research (e.g., Abdollahi et al, 2018;Matheson & Anisman, 2003;Whatley et al, 1998).…”
Section: Zero-order Correlationssupporting
confidence: 91%
See 2 more Smart Citations
“…This was somewhat surprising, given the abundance of past research indicating that diet may be predictive of cognition (e.g., Freeman, Haley-Zitlin, Rosenberger, & Granholm, 2014), coping (e.g., Kuczmarski et al, 2017), and depression (e.g., O'Neil et al, 2014). The present findings also revealed that both dimensions of cognitive flexibility (cognitive control and cognitive resources) were highly correlated, and that both dimensions were negatively associated with emotion-focused coping, typical and atypical depressive symptoms, and that only cognitive resources was positively correlated with problem-focused coping, which is in line with previous research (Gabrys, Anisman, & Matheson, 2018). In addition, persistent use of emotion-focused coping was related to both types of depression, and problem-focused coping was negatively related to typical depressive symptoms, which again corresponded with past research (e.g., Abdollahi et al, 2018;Matheson & Anisman, 2003;Whatley et al, 1998).…”
Section: Zero-order Correlationssupporting
confidence: 91%
“…This positive relation between a non-prudent dietary pattern and emotion focused coping is in line with previous research (Kuczmarski et al, 2017). Again, given the possibility that the dietary pattern and genotype might produce excessive amounts of inflammation and impair cognitive flexibility, this impairment may also contribute to persistent use of emotionfocused coping strategies, as individuals who are less flexible in the use of their coping methods tend to endorse emotion-focused coping strategies to a greater degree (Gabrys, Anisman, & Matheson, 2018).…”
Section: Interactive Effects Of Genotype Sex and Dietary Patternsupporting
confidence: 87%
See 1 more Smart Citation